1998
DOI: 10.1097/00002030-199817000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV-1 nucleic acid and HIV-1 antibodies in needles and syringes used for non-intravenous injection

Abstract: This analysis demonstrates that the risk of transmitting HIV from syringes that have been used for intramuscular or subcutaneous injection may be low, but is not zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…One study found HIV-RNA in three of 80 syringes after subcutaneous or intramuscular injections of infected patients; since the volume of blood in the syringes was too low to explain the observed HIV-RNA, the study team hypothesized that the RNA had been released by follicular dendritic cells into interstitial¯uid 92 .…”
Section: Hiv Survival and Transmission Through Medical Instrumentsmentioning
confidence: 99%
“…One study found HIV-RNA in three of 80 syringes after subcutaneous or intramuscular injections of infected patients; since the volume of blood in the syringes was too low to explain the observed HIV-RNA, the study team hypothesized that the RNA had been released by follicular dendritic cells into interstitial¯uid 92 .…”
Section: Hiv Survival and Transmission Through Medical Instrumentsmentioning
confidence: 99%
“…8 The likelihood of encountering blood in syringes or needles that have been used for medically indicated intramuscular injection of HIV-1-infected patients in the USA has been estimated by PCR (with a mean limit of sensitivity of 0·09 L to detect viral DNA from white blood cells) and enzyme immunoassay (with a mean limit of sensitivity of 0·00084 L to detect antibodies to HIV-1). 9 In one study, 10 none of 184 syringes or needles tested positive for blood with the PCR assay, and only ten (5%) tested positive when the enzyme immunoassay was used. Furthermore, none of the needles or syringes was positive for HIV-1 DNA, as judged by an assay sensitive enough to detect proviral DNA with single-copy sensitivity.…”
mentioning
confidence: 96%
“…Furthermore, none of the needles or syringes was positive for HIV-1 DNA, as judged by an assay sensitive enough to detect proviral DNA with single-copy sensitivity. In a subsequent study 10 of 80 needles or syringes tested with a nested PCR assay capable of detecting two infectious units of viral RNA, 66 of which had been used for intramuscular injection and 14 for subcutaneous injection, three (4%) were positive. However, the identification of HIV-1 RNA means only that the equipment is potentially infectious, since the assay does not identify whether the nucleic acid is from whole, or viable, virus.…”
mentioning
confidence: 99%
“…Although the estimated per-act transmission risk from unprotected exposure to a partner known to be HIV infected is relatively low for different types of exposure (Table 1), different nonoccupational exposures are associated with different levels of risk (71)(72)(73)(74)(75)(76)(77)(78)(79). The highest levels of estimated per-act risk for HIV transmission are associated with blood transfusion, needle sharing by injection-drug users, receptive anal intercourse, and percutaneous needlestick injuries.…”
Section: Transmission Risk From the Exposurementioning
confidence: 99%
“…However, these injuries typically involve smallbore needles that contain only limited amounts of blood, and the viability of any virus present is limited. In a study of syringes used to administer medications to HIV-infected persons, only 3.8% had detectable HIV RNA (72). In a study of the viability of virus in needles, viable virus was recovered from 8% at 21 days when the needles had been stored at room temperature; <1% had viable virus after 1 week of storage at higher temperatures (73).…”
Section: Transmission Risk From the Exposurementioning
confidence: 99%